Le journal personnel en tant que dispositif critique et didactique - Lis, Jerzy (Wydawnictwo Naukowe UAM, 2001)
An intimate diary is not only and exclusively spontaneous form of writing on personal themes, but may also appear as an instrument of critical reflection, and as a didactic aid. On the example of scientfic works of Philippe Lejeune and a handbook for pupils who have learning difficulties, the author analyses directions of development of this form of autobiographical recording and possibilities of using a diary in domains other than writing literature.
Personal diary as a critical and didactic instrument